Equilibrium swelling behavior and elastic properties of polymer-clay nanocomposite hydrogels - ABDURRAHMANOĞLU, SUZAN (WILEY-BLACKWELL, 2008)
Nanocomposite hydrogels were prepared by free-radical polymerization of the monomers acrylamide (AAm), NN-dimethylacrylamide (DMA), and N-iso-propylacrylamide (NIPA) in aqueous clay dispersions at 21 degrees C. Laponite XLS was used as clay nanoparticles in the hydrogel preparation. The hydrogels based on DMA or NIPA monomers exhibit much larger moduli of elasticity compared with the hydrogels based on AAm monomer. Calculations using the theory of rubber elasticity reveal that, in DMA-clay or NIPA-clay nanocomposites, both the effective crosslink density of the hydrogels and the functionality of the clay particles rapidly increase with increasing amount of Laponite up to 10% (w/v). The results suggest that DMA-clay and NIPA-clay attractive interactions are stronger than AAm-clay interactions due to the formation of multiple layers on the nanoparticles through hydrophobic associations. It was also shown that, although the nanocomposite hydrogels do not dissolve in good solvents such as water, they dissolve in dilute aqueous solutions of acetone or poly(ethylene oxide) of molecular weight 10,000 g/mol, demonstrating the physical nature of the crosslink points. (c) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 109: 3714-3724,2008
Keywords: nanocomposite hydrogels; clay; swelling elasticity; HIGH MECHANICAL STRENGTH; LAPONITE DISPERSIONS; SPATIAL INHOMOGENEITY; LIGHT-SCATTERING; GELATION; GELS; POLY(N,N-DIMETHYLACRYLAMIDE); POLY(N-ISOPROPYLACRYLAMIDE)